Giant cell tumour of bone: analysis of risk factors for recurrence in 354 patients. (1st May 2023) - Aoude, Ahmed; Nikomarov, David; Perera, Jonathan R.; Ibe, Izuchukwu K.; Griffin, Anthony M.; Tsoi, Kim M.; Ferguson, Peter C.; Wunder, Jay S.
Abstract : Aims: Giant cell tumour of bone (GCTB) is a locally aggressive lesion that is difficult to treat as salvaging the joint can be associated with a high rate of local recurrence (LR). We evaluated the risk factors for tumour relapse after treatment of a GCTB of the limbs. Methods: A total of 354 consecutive patients with a GCTB underwent joint salvage by curettage and reconstruction with bone graft and/or cement or en bloc resection. Patient, tumour, and treatment factors were analyzed for their impact on LR. Patients treated with denosumab were excluded. Results: There were 53 LRs (15%) at a mean 30.5 months (5 to 116). LR was higher after curettage (18.4%) than after resection (4.6%; p = 0.008). Neither pathological fracture (p = 0.240), Campanacci grade (p = 0.734), soft-tissue extension (p = 0.297), or tumour size (p = 0.872) affected the risk of recurrence. Joint salvage was possible in 74% of patients overall (262/354), and 98% after curettage alone (262/267). Of 49 patients with LR after curettage, 44 (90%) underwent repeated curettage and joint salvage. For patients treated by curettage, only age less than 30 years (p = 0.042) and location in the distal radius (p = 0.043) predicted higher LR. The rate of LR did not differ whether cement or bone graft was used (p = 0.753), but may have been reduced by the use of hydrogen peroxide (p = 0.069). Complications occurred in 15.3% of cases (54/354) and did not differ by treatment. Conclusion: Most patients with a GCTB can undergo successful joint salvage by aggressive curettage, even in the presence of a soft-tissue mass, pathological fracture, or a large lesion, with an 18.4% risk of local recurrence. However, 90% of local relapses after curettage can be treated by repeat joint salvage. Maximizing joint salvage is important to optimize long-term function since most patients with a GCTB are young adults. Younger patients and those with distal radius tumours treated with joint-sparing procedures have a higher rate of local relapse and may require more aggressive treatment and closer follow-up. Cite this article: Bone Joint J  2023;105-B(5):559–567.